Optimal design of low-energy transfers to highly eccentric frozen orbits around the moon - Gibbings, Alison; Zuiani, Federico; Vasile, Massimiliano; Novak, Daniel (2010)
Scheduled for launch in 2014-2015, the European Student Moon Orbiter (ESMO) offers the opportunity for University students across Europe to design and build a microsatellite. Through the use of an all-day-piggy-back launch opportunity, ESMO will exploit the relative benefits of a Weak Stability Boundary (WSB) transfer to reach the Moon. ESMO will then enter a highly elliptical frozen orbit, gathering high resolution images of the surface of the South Pole. This paper will present ESMO’s optimal WSB transfer and insertion into its desired orbit. Highly elliptical frozen orbits have the benefit of a low orbital insertion delta-V that is combined with no or very small long-term variations of eccentricity and argument of periapsis. This significantly reduces the requirements on orbit maintenance. Coupled with the mission & scientific requirements, a highly elliptical frozen orbit is considered to be the optimal orbit design for ESMO. Furthermore, an optimal multi-burn strategy for both Earth departure and lunar arrival is also added to the transfer. This is to minimise gravity losses, error in the navigation budget and to provide flexibility in the final launch date selection. ESMO is considered to be an ambitious mission design.